A palaeoenvironmental history of the southern Bekaa Valley and the Lebanon Mountains, Lebanon during the last glacial period (~ 112-35 ka BP) - Jeffers, D (2014)
The remnant montane forests of southern Lebanon provide habitat to a rich diversity of endemic, rare and threatened plant and animal species. Prior to the intensification of human activity during the mid-Holocene period these forests covered most of the Lebanon and Anti-Lebanon Mountain ranges. What is not known is how the dynamics of these forests changed in response to major shifts in climate. The aim of this DPhil thesis was to document changes in vegetation composition in southern Lebanon during the last glacial period (~112 to 35 ka BP). To achieve this aim, a palynological study was conducted on a sedimentary sequence recovered from Aammiq Wetland located in the Bekaa Valley, Lebanon. Fossil pollen was analysed to reconstruct variability in vegetation composition and abundance. Energy dispersive spectroscopy, magnetic susceptibility and loss-on-ignition were used to reconstruct the geomorphological and hydrological processes acting within the wetland and its watershed. Macro and microcharcoal were analysed to reconstruct local and regional fire histories respectively. A chronology was established for this sequence using a combination of radiocarbon and optically stimulated luminescence dating (OSL) techniques. The results indicate significant variability in the composition and abundance of vegetation through the time interval ~ 112 to ~ 35 ka BP closely aligned in time to global and regional climatic events. Changes in the chemical and physical properties of the sediments indicate significant variability in landscape erosion processes and hydrological conditions in the watershed and within the wetland over the similar interval in time. Peaks in local and regional fire activity were concurrent with periods of precession minima and Dansgaard-Oeschger warming events and had a significant impact on the composition of vegetation within the Aammiq region. These findings provide the first account of environmental change in the southern Bekaa Valley and adjacent slopes of the Lebanon Mountains during the last glacial period.